2021
DOI: 10.1177/23259671211017467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Capsular Closure After Hip Arthroscopy for Femoroacetabular Impingement Syndrome on Achieving Clinically Meaningful Outcomes: A Meta-analysis of Prospective and Comparative Studies

Abstract: Background: Recent literature has demonstrated conflicting evidence as to whether capsular closure after hip arthroscopy for femoroacetabular impingement syndrome (FAIS) results in superior outcomes compared with capsulotomy without repair. Additionally, these studies have not explored the effect of capsular management on clinically significant outcome improvement. Purpose: To perform a meta-analysis of prospective and comparative studies to determine whether capsular management influences the rate of clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Patients who underwent capsular closure after interportal capsulotomy were more likely to achieve the MCID for the mHHS score postoperatively than those who underwent no closure. This inding is in keeping with a recent review of 5 comparative studies by Kunze et al who found that interportal capsulotomy closure appeared to result in clinically improved outcomes postoperatively, although similar to this review, these results were not statistically signiicant [23]. The irst randomized controlled trial on this topic published recently by Bech et al showed no diference between groups at inal follow-up for pain and functional outcomes [4].…”
Section: Discussionsupporting
confidence: 89%
“…Patients who underwent capsular closure after interportal capsulotomy were more likely to achieve the MCID for the mHHS score postoperatively than those who underwent no closure. This inding is in keeping with a recent review of 5 comparative studies by Kunze et al who found that interportal capsulotomy closure appeared to result in clinically improved outcomes postoperatively, although similar to this review, these results were not statistically signiicant [23]. The irst randomized controlled trial on this topic published recently by Bech et al showed no diference between groups at inal follow-up for pain and functional outcomes [4].…”
Section: Discussionsupporting
confidence: 89%
“…The blood in the femoral head and neck is mainly supplied by the four groups of retinaculum arteries that originate from the medial and lateral circumflex arteries. These medial and lateral circumflex arteries pass through the attachment of the joint capsule at the femoral neck and supply more than 70% of the blood to the femoral head after entering the capsule [ 35 , 36 ]. The increase in IAP can damage the blood flow to the femoral head and may lead to osteonecrosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vidyadhar evaluated the correlation between IAP and epiphyseal perfusion pressure using a pig model and believed that decompression and IAP reduction could reduce the risk of avascular necrosis in patients with intra-articular proximal femoral fractures who underwent hip capsulotomy [ 15 ]. A meta-analysis study showed whether to suture the joint capsule has no significant effect on the post-operative function after hip arthroscopy [ 35 ]. Therefore, in the present study, the joint capsule was not sutured after hip arthroscopy to reduce the pressure in the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis assessing the effects of capsular closure following hip arthroscopy reported significantly higher rates of achieving the minimally clinical important difference for the mHHS (relative risk 1.0 (95% confidence interval (CI) 1.01 to 1.1); p = 0.001) when the capsule closed versus when it was not closed. 102 However, another review concluded that no difference in reoperation rates could be found between the two groups. 103 In addition, one study compared partial and complete repair of the capsule and found there to be a 13% revision arthroscopy rate in the partial repair group, in contrast to 0% within the complete repair group.…”
Section: Introductionmentioning
confidence: 98%